Peran Lokasi Bisnis dalam Meningkatkan Usaha : Studi Kasus UMKM Jus Segar dan Sehat di Kota Medan - Pebiola Silalahi; Nesmada Putri Manulang; Gladis Novita Malau; Jhon Veriyanto Siregar; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Business location plays a crucial role in determining the success and development of a business, particularly for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze how business location influences the performance and sustainability of the Fresh and Healthy Juice MSME in Medan. The research method used is a qualitative descriptive approach, with data collection techniques through direct observation, interviews with business owners, and documentation of daily business activities. The results show that selecting a strategic location, namely on the main road and close to busy areas such as markets, schools, and offices, has a positive impact on increasing the number of customers and sales volume. Factors such as easy transportation access, environmental cleanliness, comfort of the place, and the attractive appearance of the store also support a positive product image in the eyes of consumers. In addition, an easily accessible location simplifies the distribution of raw materials and expands opportunities for word-of-mouth promotion. Based on the analysis, it can be concluded that the right business location is an important strategy in increasing competitiveness and business revenue. Therefore, for MSMEs, selecting a location that suits the target market needs to be carefully considered so that the business can grow sustainably.